Classification of software risks with discriminant analysis techniques in software planning development process - Elzamly, Abdelrafe; Hussin, Burairah; Abu Naser, Samy S.; Doheir, Mohamed A. S. (SERSC, 2015)
The aim of this study is to propose the discriminant analysis (DA) techniques to classify and manage risks in software planning development process. These techniques are used to test the controls to each of risks to determine and classify if they are effective in mitigating the occurrence of each risk planning factor. We classified risks to three levels by predicted group membership. Also top ten risks planning software development were mitigated by using controls based on discriminant analysis techniques.